Five new thelotremoid Graphidaceae from the Philippines - Plata, Eimy Rivas; Sipman, Harrie J. M.; Lücking, Robert (Phytotaxa, 2014)
Five new species of thelotremoid Graphidaceae are described from the Philippines: Myriotrema subviride Rivas Plata, Sipman & Lücking, differing from Myriotrema viride in the more prominent ascomata and transversely septate ascospores; Ocellularia gigantospora Rivas Plata, Sipman & Lücking, differing from O. ripleyi in the uncarbonized, ecolumellate ascomata and the larger ascospores; O. leucocavata Rivas Plata, Sipman & Lücking, differing from O. cavata in the uncarbonized ascomata and the larger ascospores; O. sublaeviusculoides Rivas Plata, Sipman & Lücking, differing from O. laeviusculoides in the erumpent ascomata with black columella; and Thelotrema philippinum Rivas Plata, Sipman & Lücking, differing from Thelotrema suecicum in the stictic acid chemistry. The new combination Ocellularia megalospora (Müll. Arg.) Lücking is also proposed. Three of the new species are based on historical collections from vanished rain forest areas on the island of Luzon and are probably extinct, emphasizing the role of herbaria in documenting biotic diversity from threatened ecosystems.